Subtidal littering: Indirect effects on soft substratum macrofauna? - AKOUMIANAKI, I.; KONTOLEFAS, P.; KATSANEVAKIS, S.; NICOLAIDOU, A.; VERRIOPOULOS, G. (Mediterranean Marine Science, 2008)
Changes in macrofauna community structure, abundance and species richness were examined both before and one year after the deployment of plastic and glass bottles at littered (litter density: 16 items / 100 m2) and non-littered (control) surfaces at three unimpacted coastal areas of the western Saronikos Gulf (Greece). In parallel, LOI% at the adjacent sediments and changes in the composition of feeding types of the megaepifauna that colonized the litter were examined across treatments. Significant changes in macrofauna community structure were demonstrated between before and after littering. At only one of the sites was there detected a significant difference in macrofauna community structure between control and littered plots after littering. This difference was linked with a significant increase in the abundance of opportunistic polychaete species and LOI% levels in the sediment surface due to the entrapment of macrophytal debris within the littered surface. The study did not show a consistent direct response of macroinfauna community to litter and the associated megafauna. Unlike the megafauna attracted by litter items, soft-substratum macrofauna is less responsive to the addition of novel hard substrates in adjacent sediments. Alternatively, it could be that the impact of littering with small items triggers a macrofauna response detectable in the long-run.